Optimizing Custom Orthopedic Implants: A Generative Design Approach in the Medical Manufacturing Industry - Denesh; Abhinav; Harish; Sivarajan S. (Scientific Research, New Technologies and Applications Vol. 3, 2024)
This review paper examines the transformative impact of generative design on the development of custom orthopedic implants in the medical manufacturing sector. By integrating advanced algorithm-driven design processes, generative design technology facilitates the creation of orthopedic implants that are precisely tailored to meet the unique anatomical and biomechanical demands of individual patients. This paper synthesizes the latest research and developments, emphasizing how generative design not only enhances the functionality and fit of these implants but also significantly increases the efficiency of their manufacturing processes. The review delves into the critical role of computational techniques such as finite element analysis and machine learning in enabling the swift prototyping of patient-specific implants. Additionally, it discusses the key practical and regulatory challenges that must be navigated to integrate this technology into clinical practice. The paper also highlights the substantial benefits, including potentially shorter recovery periods and lower rates of surgical revisions. By offering a detailed overview of the current trends and prospective advancements, this paper underscores the revolutionary potential of generative design in reshaping orthopedic surgery and improving patient outcomes.